PENGARUH ATRAUMATIC CARE: AUDIOVISUAL DENGAN PORTABLE DVD TERHADAP HOSPITALISASI PADA ANAK - Rifka Putri Andayani (Menara Ilmu, 2019)
Shifting attention to the child prior to the invasive action needs to be done to reduce anxiety and reduce the impact of trauma and hospitalization in children. Distraction techniques that can be used as atraumatic care in children using audio visual with portable DVD. The study was conducted using quasi-experimental method with 26 samples of children treated in South 3rd floor of Teratai. Data were analyzed using independent t test. The results of this intervention proved to have benefits in reducing the impact of anxiety during medical and nursing actions, sex (p value 0.623), medical diagnosis (p value 0,53), and age (p value 0.003) indicating a significant relationship between anxiety with the application of atraumatic care using visual audio with portable DVD. This intervention is expected to be continued into a routine therapy program that will be conducted in the 3rd floor south lottery ward. Keywords: Atraumatic care, audio visual, hospitalization, portable DVD